Billroth I Technique Application After Resection of Gastric Leiomyoma in a Dog - Ferreira, Paulo Geovane de Cantuário; Cunha, Leonardo Inocêncio; Machado, Júlia Caroline Assis; Macedo, Maysa Alves; Stolf, Luiz Caian; Silva, Daniel Barbosa da; de Ávila Filho, Saulo Humberto (Acta Scientiae Veterinariae, 2020)
Background: Gastric neoplasia is rare, corresponding to less than 1% of cases, with a lower prevalence of those involving smooth muscle tissues. In these cases, clinical signs worsen in the occurrence of pyloric obstruction, leading to clinical manifestations such as chronic emesis. The exeresis of the neoplasm is promoted as a therapeutic measure to reestablish gastrointestinal flow. There partial gastrectomy followed by gastroduodenal anastomosis, using the Billroth I technique, is among the available surgical techniques. The therapeutic success of the Billroth I technique after pylorectomy was reported in a dog with gastric leiomyoma. Case: Canine, poodle, 9 years old, 9.5 kg, with a history of chronic vomiting starting three months ago, progressive weight loss, and melena, previously treated by another Veterinarian as idiopathic gastroenteritis. The physical evaluation of the animal showed a state of normal consciousness, body score 4/9, pale ocular and oral mucous membranes, respiratory rate 20 mpm, heart rate 166 bpm, a rectal temperature of 37.9 °C, and dehydration degree of 8.0%. Blood count showed normocytic normochromic anemia and leukocytosis with shift to the right. Radiographic and endoscopic examinations were not noteworthy. Endoscopic biopsy after a histopathological evaluation showed no cellular or tissue atypia. On the other hand, abdominal ultrasound assessment revealed thickening with loss of echotexture and definition of the muscular layer of the gastric wall, pyloric and duodenum region compatible with benign antral muscle hypertrophy and/or pyloric neoplasia. The animal worsened five days after the initial treatment, with progressive episodes of emesis and melena, opting for an exploratory laparotomy. A mass of firm consistency measuring approximately 2.5 × 6.0 cm in diameter was found in the pyloric region, opting for a pylorectomy. The excised fragment was sent for histopathological examination. Then, gastroduodenal anastomosis was performed using the Billroth I technique. After the surgery, a pasty diet was introduced orally, without using gastroenteric tubes. Dry food was offered ten days after the surgical procedure. The animal returned for clinical reevaluation on the fifteenth day and was clinically well. Histopathological examination revealed a diagnosis of gastric leiomyoma. Discussion: The casuistry of gastric neoplasia in dogs has a low incidence, with an occurrence of less than 1%, with adenocarcinoma being the most common type. However, there are less frequent reports of other gastric neoplasia, such as smooth muscle tumors. Abdominal ultrasonography is indicated for the diagnosis of gastrointestinal changes, proof of which ultrasonography was of paramount importance in this case. The surgical procedure of pylorectomy guaranteed a margin of one centimeter, meeting the principles of oncological surgery. Absorbable monofilament suture materials are the choice for the synthesis stage in hollow organs, being used in this case. The most-reported expected complications of gastrointestinal surgeries aiming at removing neoplasms are vomiting, anorexia, melena, hematochezia, hematemesis, necrosis with anastomotic ulceration, and, consequently, septic peritonitis, which were not reported in this case. The life expectancy of patients with gastric neoplasia is quite variable, with longer survival in cases of benign neoplasia. Therefore, the type of neoplasia in this case, together with the appropriate choice of therapy and the appropriate performance of the technique, was important for the good result achieved.